How to survive America - Hughley, D. L. (Darryl L.), 1963-; Moe, Doug (Comedian) (Custom House, an imprint of William Morrow, an imprint of HarperCollins Publisher, 2021)
As COVID-19 gripped America, we learned that African American communities were being disproportionately infected and killed by the pandemic. Minority communities lag behind in access to medical care, healthy food, clean air and water, mental health care, education, and more. D.L. Hughley does a deep dive into the white lies surrounding Black public health, resulting in a lively work of social commentary that's essential for understanding race relations in America today. D. L. Hughely offers a fearless satire that exposes racism's unjust tole on our bodies and minds. --